2020
DOI: 10.1186/s12882-020-02125-9
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of Angioimmunoblast T-cell lymphoma presenting with type II Cryoglobulinemia and acute kidney injury: a case report and narrative review of the literature

Abstract: Background Angioimmunoblastic T cell lymphoma (AITL) is an infrequent hematological malignancy with variable and often atypical presentations. The presence of dysproteinemia, autoantibodies and systemic involvement in AITL has often led to a delay in diagnosis or even misdiagnosis in practice. We herewith present a case of AITL that primarily presented with acute kidney injury associated with type II Cryoglobulinemia, the underlying cause was only identified 8 months after the emergence of init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Based on the majority of reviewed studies, CV patients typical exhibit MPGN as the prevailing renal histopathological lesion, which aligns with findings from other researches [7, 25]. Additionally, the studies reviewed also reported cases of focal or diffuse proliferative glomerulonephritis, mesangio-capillary glomerulonephritis, and endocapillary proliferative glomerulonephritis [19, 20, 26–29]. The presence of CV-related acute nephritic or nephrotic syndrome significantly increases the risk of severe cardiovascular events, while chronic renal failure or ESKD is associated with a substantial increase in mortality [30, 31].…”
Section: Discussionsupporting
confidence: 80%
“…Based on the majority of reviewed studies, CV patients typical exhibit MPGN as the prevailing renal histopathological lesion, which aligns with findings from other researches [7, 25]. Additionally, the studies reviewed also reported cases of focal or diffuse proliferative glomerulonephritis, mesangio-capillary glomerulonephritis, and endocapillary proliferative glomerulonephritis [19, 20, 26–29]. The presence of CV-related acute nephritic or nephrotic syndrome significantly increases the risk of severe cardiovascular events, while chronic renal failure or ESKD is associated with a substantial increase in mortality [30, 31].…”
Section: Discussionsupporting
confidence: 80%
“…The commonest type of B-cell lymphoma is the DLBCL, but other forms of B-cell lymphoproliferative disease have been described, including mixed type II cryoglobulinemia and small lymphocytic lymphoma/chronic lymphocytic leukemia. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 The development of secondary B-cell lymphomas with a DLBCL morphology may portend a more aggressive clinical course with multiple sites of lymphomatous dissemination, including bone marrow, duodenal bulb, lung, ileum, soft tissue, and skin. 3 , 4 , 5 , 6 , 7 , 8 …”
Section: Discussionmentioning
confidence: 99%